THE INFLUENCE OF THE IMMUNE RESPONSE ON LIVER FIBROSIS PROGRESSION IN CHRONIC LIVER DISEASES – A REVIEW ARTICLE - Vujović, Ankica; Djelic, Marina; Milosevic, Ivana (Medicinski podmladak, 2024)
Chronic Liver Disease (CLD) is presented by continuous inflammation, destruction and regeneration of hepatocytes lasting more than six months. The progression leads to fibrosis, liver cirrhosis and, in the most severe cases, hepatocellular carcinoma (HCC). The role of the immune system in CLD was recognized several decades ago, but not all the immune mechanisms of liver damage, which could be significant as potential therapeutic options, have been elucidated to date. Cytokines of the interleukin (IL)-23/IL-17 axis have been described as the key cytokines involved in the immunopathogenesis of CLD. Numerous studies have described the influence of the IL-23/IL-17 axis on the development of liver fibrosis with heterogeneous results. These results mainly described the pathophysiology, but also and potential immunotherapeutic options. The most contradictory results published in current studies concern chronic hepatitis C (HHC) and nonalcoholic steatohepatitis (NASH). It is still unclear whether there are variations in local and systemic proinflammatory cytokine concentrations in HHC which can potentially guide immunotherapeutic strategies in these patients. On the other hand, in NASH inflammation is one of the key drivers of disease progression and development of fibrosis. The regulation of inflammation is controversial, depending on several intrahepatic and extrahepatic factors, and so far the mechanisms of immunopathogenesis have not been clearly revealed even in this chronic liver disease. Further research is needed to clearly suggest whether some of the immunohepatotoxicity significant mechanisms in chronic liver diseases could be a potential prognostic and immunotherapeutic factor. Key words: chronic hepatits C, non-alcoholic steatohepatitis, inflamation